Desolvation induced crystal jumping: reversible hydration and dehydration of a spironolactone–saccharin cocrystal with water as the jumping-mate. Issue 39 (24th September 2021) - Chen, Yifu; Jing, Bo; Chang, Zewei; Gong, Junbo
Abstract : We present a spironolactone–saccharin cocrystal hydrate as the first example of a crystal that jumps without changes in either the lattice parameter or the molecular conformation to highlight the unique advantages of the jumping-mate strategy. Abstract : A jumping crystal of the channel-type hydrate of spironolactone–saccharin cocrystals was presented as the first example of a crystal that jumps without changes in both the lattice constant and the molecular conformation, emphasizing the general applicability of our newly proposed design concept that introduces an easy-to-escape component, the jumping-mate, to generate crystal motions.